Relations of exhaled nitric oxide and FEV1 to personal endotoxin exposure in schoolchildren with asthma. Issue 12 (16th June 2015) - Delfino, Ralph J; Staimer, Norbert; Tjoa, Thomas; Gillen, Daniel L
Abstract : Background: Asthma prevalence and acute exacerbations have been associated with endotoxin exposure. However, there are limited data on relations between acute asthma outcomes in children and personal exposure to endotoxin or whether this relation is modified by personal air pollution exposures. Methods: We made repeated measurements of the fractional concentration of exhaled NO (Fe NO ), forced expiratory volume in 1 s (FEV1 ) and personal endotoxin exposures in patients with persistent asthma aged 9–18 years, each of whom was followed for 10 consecutive days in Riverside and Whittier, California. Endotoxin was measured in PM2.5, and simultaneously we measured personal exposure to air pollutants: NO2 and PM2.5 mass, elemental carbon and organic carbon. Endotoxin exposure–response relations and interactions between endotoxin and air pollutants were analysed with mixed models controlling for personal temperature, humidity and the 10-day period. Results: Neither percent-predicted FEV1 nor Fe NO was associated with personal endotoxin overall; however, endotoxin was associated with FEV1 among patients with average percent-predicted FEV1 <80%. When NO2 was above its median, Fe NO increased by 2.2% (95% CI −0.8% to 5.2%) for an interquartile increase in personal endotoxin, whereas Fe NO was lower by −1.8% (95% CI −4% to 0.5%) when NO2 was≤its median. However, this is out of 12 interaction tests between personal endotoxin and a binary air pollutant for each outcome (FEV1 and Fe NO ), and there were no interactions with any continuous-scaled pollutant. Conclusions: Personal endotoxin exposure was not associated with acute daily changes in Fe NO or FEV1 in a cohort panel of schoolchildren with asthma, except for decreased FEV1 among patients with more severe asthma (percent-predicted FEV1 <80%). There was limited evidence of effect modification of endotoxin by personal exposure to air pollution.